When East meets West: the impact of national cultural differences on Asia Pacific Acquirers’ performance improvement - Pham, Dong Nghi (2017)
The dissertation investigates the net effect of national cultural difference on long-term performance improvement of acquirers from Asia Pacific compared to those from North American & Western Europe. It is a counterbalance to the current double-layered bias in culture difference researches in term of negativity-focused conceptual vein and Western-dominated empirical sample. Positive and negative impacts of national cultural difference is reframed into an integrating framework. The empirical study is conducted on two samples consisted of 859 cross-border M&As in total during a 5-year period from 2009 to 2014, accounted for several country-, firm-, time-, and deal-level effects. My results show that while M&A into a culturally distant country would have an adverse impact on performance enhancement of Western acquirers, they do not dampen performance improvement of acquirers from Asia Pacific. This supports the hypothesis that due to their Cultural, Institutional, Psychological, and Behavioural attributes, AP acquirers can better mitigate negative impacts of CD whilst better leveraging CD’s positive influences.